Computer-Aided Power System Fault Analysis - Ekici, Sami (Wiley, 2011)
Most of power systems courses contain mathematical analysis, animations, simulations, and technical tours to power stations. However, experimental studies particularly in fault analysis are very difficult due to high voltages and currents passed through short circuits. Although there are experimental equipments and prototype systems for the students, they are very expensive. This paper presents a new computer-aided approach for power system analysis course at The University of Firat. The new course covers the previous course which contains only a short experiment by using a prototype power system. The sequence of new updated course for high-voltage fault analysis is following: experimental implementations, simulation, signal processing and fault classification. A questionnaire containing II questions has been applied to students to determine the effectiveness of the new course. According to questionnaire; the updated course has been found more useful to analyze and understand the transmission line faults than the previous course. (C) 2009 Wiley Periodicals, Inc. Comput Appl Eng Educ 19: 66-70, 2011; View this article online at wileyonlinelibrary.com; DOI 10.1002/cae.20290
Keywords: power systems; fault analysis; signal processing